Analysis of The Implementation of The Unified Theory of Acceptance and Use Technology and The Delone & Mclean Model to Identify User Satisfaction of The Digital Wallet Application - Suryati; Budiman, Yusuf Unggul; Sutartiah, Farliana; Hadayanti, Didit; Judijanto, Loso (SEULANGA SYSTEM PUBLISHER, 2023)
This research aims to see how to determine the factors of user satisfaction and trust in e-wallets. This study uses a quantitative approach. The analysis in this research involved data collection and statistical analysis. The research population and sample collection technique were carried out using purposive sampling. In this study, there was a sample of 100 people. Data collection was carried out by distributing surveys in the form of questionnaires aimed at e-wallet user respondents. Meanwhile, statistical analysis was carried out to test the outer and inner models. Data analysis is divided into two categories: demographic data analysis and inferential statistical analysis using Microsoft Excel. Based on the results of data analysis and discussion, it can be concluded as follows: Users are satisfied with the use of e-wallets because they are helped by the service, which gives a good impression to the user. Users feel confident in using e-wallets because they provide security but lack the quality of the application, which still has problems with several features.